PENGARUH GREEN MARKETING DAN GREEN PACKAGING TERHADAP PERILAKU KONSUMEN GUARDIAN SUPERMARKET SURABAYA - Mulyono, Franky Prasetyo; Sulistyowati, Raya (Program Studi Pendidikan Tata Niaga Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2024)
The reason of this study is think about the effect of green marketing and green packaging on consumer behavior at Guardian Supermarket Royal Plaza Surabaya. The sample consisted of 330 respondents who were visitors to the Guardian who had purchased at the Guardian, knew about green marketing and green packaging at the Guardian. The sampling technique used is purposive sampling. Data collection techniques used online questionnaires in the form of Google forms, data analysis using SmartPLS 3.0 software. The comes about of this think about demonstrate that green marketing incorporates a positive effect on consumer behavior and green packaging features a positive impact on comsumer behavior.